Building a low cost advanced driver assistance system – road lane detection - Huang, Junjia (2018)
The road lane detector presented in this program is to detect the road lane lines and their boundaries by processing the image or video captured by a car camera. This is a pipeline software which using python with OpenCV to conduct the image processing. It eliminates the distortion, isolates the road lane lines with a combined filter and inverse perspective mapping transform. The algorithm can detect the road lane lines in still image and video with good range of visibility and lighting condition.